Preoperative identification of the risk factors of cervical lymph node metastasis in medullary thyroid carcinoma - Wang, Yitong; Chen, Jiahui; Gao, Xuemeng; Huang, Ying (Frontiers in Endocrinology, 2025)
This research aimed to investigate the preoperative risk factors for lymph node metastasis (LNM) in medullary thyroid carcinoma (MTC) using clinical, pathological, serological, ultrasound, and radiomics characteristics. Additionally, it aimed to explore the diagnostic precision of ultrasound (US) for MTC and LNM. A retrospective analysis of 111 nodules was eligible from 104 patients from January 1, 2000, to December 28, 2024. Based on the presence of LNM, they were divided into Group 1 (with LNM, n=51 nodules from 44 patients) and Group 2 (without LNM, n=60 nodules from 60 patients). Three predictive models were constructed: (1) Model 1: incorporating clinical, pathological, serological, ultrasound features; (2) Model 2: utilizing only radiomics features; and (3) Model 3: combining all the above features. The AUC values for the three models were 0.759, 0.97, and 0.97, respectively. The nomogram for Model 1 achieved a C-index of 0.707. Additionally, we evaluated the diagnostic efficacy of ultrasound for MTC, lymph node enlargement, and metastasis. Results indicated that patients with symptoms on admission, multifocality, and solid lesions in MTC were at increased risk of LNM. The nomogram and radiomics features significantly improved the predictive performance. Our study provides a strong basis for predicting LNM.